D PERAN PEMIMPIN DAN MANAJER PENDIDIKAN DALAM REFORMASI KEBIJAKAN (KEPEMIMPINAN STRATEGIS DAN TRANSFORMASIONAL BERBASIS TEKNOLOGI) - Agus Fidyani; Fani Raihan Fadilah; Ibnu Hajar Al Ashqolani; Masduki Duryat (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the role of educational leaders and managers in supporting policy reform through the implementation of technology-based strategic and transformational leadership. In the digital era, educational institutions are required to adapt to dynamic policy changes, thus requiring visionary, adaptive, and innovative leadership. The research method used is a qualitative approach with literature studies and descriptive analysis of various scientific sources related to educational leadership and digital transformation. The results show that educational leaders have a crucial role in formulating strategic visions, managing organizational change, and integrating technology into decision-making and learning processes. Transformational leadership has been shown to improve the motivation, performance, and participation of all stakeholders in the implementation of educational policies. Meanwhile, the use of technology strengthens management effectiveness, transparency, and accountability in the education system. Thus, the synergy between strategic, transformational, and technology leadership is key to the success of sustainable educational policy reform.